TEACHER’S SPEECH AS A COMMUNICATIVE TOOL (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Teacher speech plays a crucial role in education, serving as a key means of communication that influences not just how information is shared, but also how the classroom atmosphere is shaped, how students participate, and the overall success of learning. This article examines the diverse roles of teacher speech, focusing on its use in delivering lessons, managing the classroom, inspiring students, providing feedback, and building strong teacher-student relationships. By referencing studies from fields such as educational psychology, linguistics, and teaching methodology, the article underscores the value of effective verbal communication in enhancing both teaching and learning. It also discusses how flexible and inclusive language practices can meet the varied needs of students and support fairness in education.